LEGAL EXPLANATION AS AN EFFORT TO INCREASE LITERATURE AWARENESS RELATED TO CHILDREN PROTECTION IN THE SAKA WIRA KARTIKA KODIM ORGANIZATION 0315/BINTAN - Novi Wira Sartika Zebua; Winda Fitri (ConCEPt - Conference on Community Engagement Project, 2022)
The provision of legal education from an early age as a supporter in realizing literacy awareness in order to achieve shared welfare is a very important forum to be developed. Children who are assets of the nation also do not escape the attention of a country with the establishment of a regulation in IndonesiaLaw Number 35 of 2014 changes to Law Number 23 of 2002 concerning child protection as an umbrella that protects a child's activities before the law. According to data released by the Ministry of Women's Empowerment and Child Protection, which was inputted through the Online Information System for the Protection of Women and Children (SIMFONI PPA), there were 3,314 cases of violence against children with a total of 3,683 children victims in the vulnerable period during January. -June 2021, this is of course very unfortunate with the presence of a law that has not given maximum results, so we are invited to first understand and understand the values ​​contained in a statutory regulation.